Single Nucleotide Polymorphism of the Interferon-γ Gene (IFN-γ +874 T/A) and the Prognosis of Hepatitis B Infection - Mohammad Sadegh Naghizadeh; Mohsen Naseri; Mohammad Fereyduni; Masoud Ziaee; Abdolghader Tane; Hamidreza Safari; Neda Mahavar; Roya Mahdavi; Gholamreza Anani Sarab (Pasteur Institute of Iran, 2018)
Introduction: Chronic Hepatitis B virus infection is a multifactorial disease with a variety of clinical outcomes. Since interferon-gamma (IFN-γ) is a significant immune factor in antiviral defense, this case-control study aimed to investigate the potential relationship between single nucleotide polymorphism of rs2430561 and hepatitis B infection outcome in a population of Birjand city, eastern Iran. Methods: Blood samples were collected from 60 chronically HBV- infected patients and 60 healthy subjects with the history of HBV infection. Genomic DNA was extracted from whole blood by the salting-out method. The first intron of IFN-γ with a length of 264 bp was amplified by Amplification Refractory Mutation System Polymerase Chain Reaction (ARMS-PCR) followed by sequencing. Results: Our results exhibited a statistically significant difference between patients and control individuals (p-value<0.001). The frequency of the allele A was 73.3% in HBV- infected patients, whereas in controls (individuals with a history of HBV infection) it was 46.7%. Conclusion: A statistically significant relationship was found between the IFN-γ (+874T/A, rs2430561) single nucleotide polymorphism (SNP) and chronic HBV infection in the studied population. The obtained results showed that HBV infected individuals with T allele have less risk of progressing to chronic HBV infection. It also suggests that the homozygous carriers of the A allele are more vulnerable to chronic HBV infection.